2017
DOI: 10.1007/s00348-017-2400-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot pressure-sensitive paint lifetime measurements on fast rotating blades using an optimized double-shutter technique

Abstract: A pressure-sensitive paint (PSP) system is presented to measure global surface pressures on fast rotating blades. It is dedicated to solve the problem of blurred image data employing the single-shot lifetime method. The efficient blur reduction capability of an optimized double shutter imaging technique is demonstrated omitting error-prone post-processing or laborious de-rotation setups. The system is applied on Mach-scaled DSA-9A helicopter blades in climb at various collective pitch settings and blade tip Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Recently, time‐resolved analysis using the emission decay profile of phosphorescent materials has been a focus for fluid dynamics, aeronautical and environmental engineering . The emission lifetime‐based PSP systems have shown significant potential for unsteady flow diagnostics of aircrafts, high‐speed vehicles and turbomachinery .…”
Section: Figurementioning
confidence: 99%
“…Recently, time‐resolved analysis using the emission decay profile of phosphorescent materials has been a focus for fluid dynamics, aeronautical and environmental engineering . The emission lifetime‐based PSP systems have shown significant potential for unsteady flow diagnostics of aircrafts, high‐speed vehicles and turbomachinery .…”
Section: Figurementioning
confidence: 99%
“…iii. Single-Shot Methods based on PSP Lifetime: A laser is used as a high-energy excitation source leading to a high SNR [19][20][21][22]. A double shutter particle image velocimetry (PIV) camera records a set of images with very short exposure times, minimizing the effects of cycle-to-cycle instabilities and blade movement.…”
Section: Psp Measurements On Rotating Bladesmentioning
confidence: 99%
“…By eliminating the “wind-off” images, we can reduce the measurement errors caused by the deformation or movement of the model and changes in the distribution of excitation light and temperature on the model between the “wind-on” and “wind-off” conditions. Much effort has been made to develop the lifetime imaging method [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, it is known that the luminescence lifetime of PSP is not spatially uniform, even under uniform pressure and temperature conditions [ 12 , 13 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much effort has been made to develop the lifetime imaging method [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. However, it is known that the luminescence lifetime of PSP is not spatially uniform, even under uniform pressure and temperature conditions [ 12 , 13 , 15 , 16 , 17 ]. Sugioka et al reported that a polymer-based PSP applied to a real wing showed considerable spatial variation in the luminescence lifetime [ 13 ].…”
Section: Introductionmentioning
confidence: 99%